(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Special education is a young field and is evolvingrapidly special education is different from regular education. It takes intoaccount the child’s intra individual and inters individual differences. Specialeducation is a profession, has its own tools, techniques, strategies andresearch efforts aimed at meeting the learning needs of exceptional children.Special education means specially designed instruction that meets the uniqueneeds of an exceptional child. The services may range from consultationprovided to the teacher of a disabled student to special education and relatedservices for special needs children. "Special is the individually plannedand systematically monitored arrangement of physical settings, specialequipment’s and materials, teaching procedures and other interventions designedto help exceptional children achieve the greatest possible personal self-sufficiencyand academic success."